2017
DOI: 10.1002/cctc.201700567
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Influence of SSZ‐13 Zeolite Pore Hierarchy in Methanol‐to‐Olefins Catalysis by Using Nanometer Accuracy by Stochastic Chemical Reactions Fluorescence Microscopy and Positron Emission Profiling

Abstract: [a] Increasingly,m ethanol is considered as an important chemical intermediate between coal and natural gas feedstocks and olefinic building blocks used extensively in the chemical industry.Currently,t he methanol-to-olefins (MTO) reaction is the most important in terms of the installed capacity of all methanol-tohydrocarbon reactions. [1][2][3][4] Am icroporous silicoaluminophosphate materialw ith the chabazite (CHA) framework topology (H-SAPO-34)i st he preferred catalystc ommercially.[5] One concern is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…4 To date, various zeolite catalysts have been used for the conversion of methanol, among which SSZ-13 zeolite with CHA framework topology exhibits high MTO catalytic performance, mostly contributed to its large surface area, useful pore structure in terms of shape selectivity, moderate acidity, and high thermal/hydrothermal stability. [5][6][7] However, the mass transfer limitation and coke species formation in the cages result in a low catalytic efficiency and the rapid deactivation of SSZ-13. 8 In order to prolong the catalytic lifetime and suppress the deactivation of SSZ-13 catalyst in the MTO reaction, various methods have been used to decrease the crystal size, which can signicantly reduce the diffusion path length and enhance the accessibility of reactants to the external active sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To date, various zeolite catalysts have been used for the conversion of methanol, among which SSZ-13 zeolite with CHA framework topology exhibits high MTO catalytic performance, mostly contributed to its large surface area, useful pore structure in terms of shape selectivity, moderate acidity, and high thermal/hydrothermal stability. [5][6][7] However, the mass transfer limitation and coke species formation in the cages result in a low catalytic efficiency and the rapid deactivation of SSZ-13. 8 In order to prolong the catalytic lifetime and suppress the deactivation of SSZ-13 catalyst in the MTO reaction, various methods have been used to decrease the crystal size, which can signicantly reduce the diffusion path length and enhance the accessibility of reactants to the external active sites.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Typical strategies for the preparation of hierarchical zeolite materials, such as alkaline treatment, does not enhance MTO catalytic performance when applied to SSZ-13, because of the decrease of surface area and acid sites. 7,12 Hensen et al 13,14 synthesized mesoporous SSZ-13 crystals by a dually structure-directing synthetic route using N,N,N-trimethyl-1adamantanammoniumhydroxide (TMAdOH) and diquaternary ammonium type surfactant as templates. They further synthesized hierarchical SSZ-13 zeolites by adding surfactant C 22À4À4 Br 2 and sodium uoride to the synthesis gel.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] More recently, it has also been reported that introduction of NaF during the synthesis of high-silica CHA zeolites results in additional (intracrystalline) microporosity, which can greatly enhance mass transport of reactants to active sites during catalysis. 13,14 Framework etching with HF or NH 4 HF 2 is another method to introduce additional porosity in zeolites. [15][16][17][18] Furthermore, substitution of surface hydroxyls with fluoride groups involving for instance organosilane grafting can be employed to enhance the surface hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol to lower olefins reaction is a critical process for conversion of nonoil resources to chemicals through methanol, and light olefins especially ethylene and propylene have been widely applied in polymerization reaction and petrochemical industry [1][2][3][4][5][6]. Several types of molecular sieves for the MTO reaction have been intensively studied, and the most typically are SAPO-34 [7,8], ZSM-5 [9][10][11], and SSZ-13 [12][13][14]. Among these catalysts, SAPO-34 has drawn the most attention due to its special framework with a CHA cage (9.4 Å) and 8-ring pore openings (0.38 Å 0.38 Å) [15], as well as mild acidity [16][17][18] which result in excellent catalytic performance [3,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%